Determining The Optimal Milk Distribution Route Using The Ant Colony Optimization Method on Milk Industry - Hakim Gusti, Mohamad Lukman; Aryanny, Enny (Spektrum Industri, 2023)
A good distribution system will ensure the availability of products or goods needed by the community. The objective of this research is to identify the most efficient route for distributing UHT milk on Milk Industry, with the goal of minimizing the overall distance traveled during distribution. The contribution of this study is to determine the optimal distribution route for UHT milk on Milk Industry. Data analysis or data calculation is done using Ant Colony optimization. The independent variables used are the initial distribution route data of the company, agent location data, product demand data, and distance data between agents. The results of this study found that the company's route resulted in a total route distance of 251.95 km while for the optimal total distance Ant Colony Optimization method is the total route distance of 230.2 km. Thus, the optimal route of the distribution of Ant Colony Optimization method is better than the initial route of the company with a total route distance savings of 21.75 km with a percentage of savings of 8.63%.